Single phase motor speed control using SPWM inverter - Siti Fairuz, Hamid (2008)
An inverter circuit by using Sinusoidal Pulse Width Modulation (SPWM) switching schemes is developed to control the speed of single-phase AC motor and being verified experimentally. Inverters are circuit that convert a DC source to an AC source. DC is one type of energy found in batteries and AC is a type of energy that is produced by the power company and found in electrical homes/offices appliances. The application of this AC motor controller is to provide single-phase ac induction motor less than ½ hp (372.85 W). Semiconductor device, Metal Oxide Field Effect Transistor (MOSFET) is used as switch in the full bridge (H-bridge) inverter configuration with unipolar voltage switching. A variable frequency output waveform is produced by the inverter to run a motor at variable speeds that are directly proportional to this frequency. Besides the MOSFETs as the inverter, driver for the MOSFET also very important in this circuit development because it is use to interface between control circuits (low voltage part) and inverter (high voltage part). Another important part in this inverter design is PICmicro microcontroller chip that is used to provide the switching schemes to the MOSFETs. This microchip acts as a controller circuit that produces the carrier signal and modulating signal for the inverter. The objective of this project is to build an ac motor speeds controller for holiday usage appliances, to simulate and analyze the single-phase SPWM operation of the inverter switching characteristics. The Programmable Interface Computer PIC used is PIC 18F4550 and the MOSFET driver used is IR2110. At the end of this project, the SPWM output is developed from the controller circuit and applied to the driver circuit and the inverter, and hence can be used to control the speed of the AC motor.